2020
DOI: 10.1039/c9ra10984f
|View full text |Cite
|
Sign up to set email alerts
|

Solid electrolyte interphase formation between the Li0.29La0.57TiO3solid-state electrolyte and a Li-metal anode: anab initiomolecular dynamics study

Abstract: An ab initio molecular dynamics study of an electrochemical interface between a solid-state-electrolyte Li0.29La0.57TiO3 and Li-metal to analyze interphase formation and evolution when external electric fields are applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Such elucidation would require much longer times of simulation and larger unit cells for better statistics; actually, it would require a totally different strategy. Therefore, the use of MSDs in our simulations is to determine the solvation of the ions but not to determine their diffusion coefficients. , This is a transient-state study and diffusion analysis would require a steady-state study; therefore, the mean-squared displacements shown in Figure cannot be used to determine any related property such as diffusion mechanisms and constants.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such elucidation would require much longer times of simulation and larger unit cells for better statistics; actually, it would require a totally different strategy. Therefore, the use of MSDs in our simulations is to determine the solvation of the ions but not to determine their diffusion coefficients. , This is a transient-state study and diffusion analysis would require a steady-state study; therefore, the mean-squared displacements shown in Figure cannot be used to determine any related property such as diffusion mechanisms and constants.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There are recent developments in the study of interfaces at batteries using directly external electric fields; some of them are presented here. Galvez-Aranda and Seminario 27 studied the Li 0.29 La 0.57 TiO 3 solid-state electrolyte in a nanobattery using ab initio molecular dynamics simulations, finding that the SSE decomposes in contact with the Li-metal, forming lithium oxide at the interface, even without the effect of the external field. Once the external field was applied with intensities from 0.5 to 2 V/Å, they found that the electric field accelerated the formation of lithium oxide at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…As is known to all, the semicircle in the high frequency region is attributed to the interface resistance of the surface membrane on the electrode active particles, and the semicircle in the medium-to-low frequency region is ascribed to the charge transfer resistance between the electrode active particles and LE. [36][37][38] In Fig. 7a, the interfacial resistance of the pristine LCO is higher than that of the 3-PHL-LCO before cycles.…”
Section: Electrochemical Characterizationmentioning
confidence: 92%
“…Liu et al [82] confirmed that black LLTO showed two new peaks at the lower binding energies corresponding to the formation of Ti 3+ with lower electron densities. Galvez-Aranda et al [83] identified that Ti reduction occurs at the LLTO/Li metal interface. The reaction rate at the interface increases as the applied external electric field increases corresponding to an electrochemical instability of the LLTO/Li-metal interface.…”
Section: Ti Reduction At the Interfacementioning
confidence: 99%